2013
DOI: 10.3109/19396368.2013.854426
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR based metabolic profiling of day 2 spent embryo media correlates with implantation potential

Abstract: Morphological assessment is currently the primary technique for selection of viable embryos for uterine transfer during assisted reproductive techniques, however this method has limited predictive power. The objective of this study was to employ NMR based metabolic profiling analysis of spent embryo culture media to identify novel biomarkers of embryo viability and provide insight into the metabolism of a viable embryo. A total of 37 patients undergoing IVF/ICSI treatment were recruited and 58 media samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
2
17
0
2
Order By: Relevance
“…The study revealed differences in CM metabolite ratios between pregnant and nonpregnant women diagnosed by urinary analysis of the β subunit of human chorionic gonadotropin (βhCG; Wallace et al, 2014). By using another spectroscopy technique, Fourier transform infrared spectroscopy ( FTIR ), we recently developed a noninvasive system that successfully predicted embryonic sex after analysis of spent CM (Muñoz et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed differences in CM metabolite ratios between pregnant and nonpregnant women diagnosed by urinary analysis of the β subunit of human chorionic gonadotropin (βhCG; Wallace et al, 2014). By using another spectroscopy technique, Fourier transform infrared spectroscopy ( FTIR ), we recently developed a noninvasive system that successfully predicted embryonic sex after analysis of spent CM (Muñoz et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…В основе попыток применения метаболомных подходов к отбору эмбрионов лежат ранние работы, в которых авторы использовали различные типы спектроскопии для анализа ЭПС [8][9][10]. Первые работы по анализу эмбриональных сред проводились с использованием ближней ИК-спектроскопии, по данным которой авторы могли сравнивать спектры поглощения образцов и соотносить их с жизнеспособностью и имплантационным Зорина и др.…”
Section: Discussionunclassified
“…[5][6][7]. В последнее время применение ряда методов спектроскопии (Рамановская спектроскопия, ЯМР-спектроскопия, ИК-спектроскопия) было использовано для изучения эмбрионального метаболома [8][9][10]. Состояние метаболома отражает динамические изменения жизнедеятельности клеток, связанные с экспрессией определённых наборов генов, и кодируемых ими белков, и является характеристикой их молекулярного Целью исследования являлось определение изменения профилей метаболитов в эмбриональных питательных средах (ЭПС) для оценки качества и имплантационного потенциала культивируемых эмбрионов человека.…”
Section: Introductionunclassified
“…The scoring system is mostly subjective in nature, which makes it difficult to standardize. As a result, the discovery of biomarkers which can be quantified (thus being more objective) has led to focusing on the levels of genomics , transcriptomics , proteomics , and metabolomics . However it must be highlighted that in this moment the morphological evaluation by light microscopy remains the primary approach of embryo assessment during IVF cycles .…”
Section: Introductionmentioning
confidence: 99%